2020
DOI: 10.7717/peerj.10611
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial variables and quality of life during the COVID-19 lockdown: a correlational study on a convenience sample of young Italians

Abstract: Background In 2020, to limit the spread of Coronavirus (COVID-19), many countries, including Italy, have issued a lengthy quarantine period for the entire population. For this reason lifestyle has changed, bringing inevitable repercussions to the Quality of Life (QoL). The present study aims to identify which psychosocial variables predict behaviors capable of affecting the QoL during the lockdown period, potentially highlighting factors that might promote well-being and health in the Italian population during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 73 publications
2
27
0
Order By: Relevance
“…We found that stress, fear of COVID-19 and to a lesser limit OCD, mediated the association between cyberchondria severity and physical QOL, whereas anxiety, stress and fear of COVID-19 mediated the association between cyberchondria severity and mental QOL. Well-being and life satisfaction have been adversely impacted by the new pandemic of COVID-19 [ 16 ]. The findings of a latest study found that there was a marked rise in pandemic issues and major behavioral changes [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that stress, fear of COVID-19 and to a lesser limit OCD, mediated the association between cyberchondria severity and physical QOL, whereas anxiety, stress and fear of COVID-19 mediated the association between cyberchondria severity and mental QOL. Well-being and life satisfaction have been adversely impacted by the new pandemic of COVID-19 [ 16 ]. The findings of a latest study found that there was a marked rise in pandemic issues and major behavioral changes [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fear of contacting people who may be infected with COVID-19 has been reported, and this, unfortunately, may intensify the damage of the disease itself [ 15 ]. People tried to cope in a socially distancing context by engaging in activities that affirm social (e.g., communicating virtually online) in order to overcome perceived threats and contagion fear [ 16 ]. These behaviors may serve as coping mechanisms for people who are scared of getting the disease, improving their well-being and therefore their quality of life [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 lockdown experiences have the potential to significantly impair core aspects of relationship maintenance by disrupting the frequency and quality of shared experiences, and interpersonal communication patterns. This could be associated with psychological consequences such as a decreased sense of closeness and a reduction in perceived relationship quality ( Aleman & Sommer, 2020 ; Lardone et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The scientific literature concerning similar pandemics, such as the SARS epidemic, demonstrated that quarantine negatively affects psychological well-being, leading to the development of post-traumatic stress symptoms (Reynolds et al, 2008;Castelli et al, 2020;Lardone et al, 2020). To this regard, there are many studies that document a strong relation between COVID-19 quarantine and the onset of stress or stress-related behaviors (Brooks et al, 2020;Lardone et al, 2020;Pisano et al, 2020;Zurlo et al, 2020) among other things, more observed in females (Mazza et al, 2020) and in those who are younger (≤40 years) (Xiong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%